FEATURES OF NEUTRAL POLYSACCHARIDES AND GLYCOGEN DISTRIBUTION IN THE STRUC-TURES OF NORMAL RAT STOMACH AND AFTER INTRAFETAL ADMINISTRATION OF ANTIGEN - Ключко, С.С.; Соколовський, Д.М. (World of Medicine and Biology, 2015)
We studied the changes in the dynamics of accumulation of glycoprotein structures of the gastric mucosa of rats in norm and after intrauterine administration of antigen. It was established that most surface glycoproteins containing a gastric mucus and the cytoplasm of epithelial cells well. Much less neutral polysaccharides and glycogen accumulates in the cytoplasm of epithelial cells of the surface, submucosal fibroblasts and connective tissue in the lamina propria of the gastric mucosa. It is proved that after the introduction of prenatal observed activation of antigen non-specific humoral local immunobiological barrier is the first to the 14th day of postnatal life, as evidenced by the increase in the accumulation of neutral polysaccharides in the stomach mucosa.
Keywords: stomach; rats; glycoproteins; antigen